Efectividad percibida de los instrumentos tradicionales e innovadores de rendición de cuentas en España. Análisis comparativo en Andalucía, Euskadi, Cataluña, Galicia, Madrid, y Valencia - Zuberogoitia Espilla, Aitor; Díaz-Campo, Jesús; Pérez-Pereiro, Marta (Estudios sobre el Mensaje Periodístico, 2020)
The perceived effectiveness of established and innovative media accountability instruments is analyzed in Andalusia, Euskadi, Catalonia, Galicia, Madrid and Valencia, and by means of a survey conducted among journalists, focus groups with media consumers in each community, and in-depth interviews with experts. Some differences are observed across professionals, citizens and experts and amongst the different autonomous communities. Audience participation in media accountability is the most controversial aspect.